أقرت أهمية القرائن في قبول الروايات وردها عند الإمام الترمذي في كتابه الجامع (نماذج مختارة من كتاب الطهارة) - Hafidi, Hakima; Omara, Siham (Jurnal Studi Al-Qur'an, 2022)
This paper is concerned with examining Imam Al-Tirmidhi’s action in accepting and refuting the narrations, in addition to weighting the differences by relying on the strengthening evidence of one aspect over the other; and other things that we mentioned in the research through selected examples from The Book of Purification “Ettahara”. What prompted us to write on this subject was what was rumoured about Imam al-Tirmidhi that he was lenient regarding discrediting and endorsement and correcting and weakening. And then the need for specialists to clarify this issue. This research used the critical analytical approach, through which we reached some results, the most important of which are: that Imam Al-Tirmidhi relied on various evidence in weighing the differences and in accepting and rejecting. As for the issue of leniency with which al-Tirmidhi was accused, we did not find any mention of it among the imams who preceded him.